Menumbuhkan Jiwa Kewirausahaan dalam Memanfaatkan Potensi Tanaman Enceng Gondok (Pemberdayaan Masyarakat di Desa Kesongo, Kab. Semarang) - Bambang Hermanu; Sofia Hertiana, Nurrahma (Universitas 17 Agustus 1945 Semarang, 2024)
In this community service activity, efforts have been made to mobilize and empower the community through Bembo Art as a motivator and facilitator. However, many people still lack the level of participation required to become independent entrepreneurs to achieve prosperity. This lack of community participation is caused by several factors, namely: firstly, many people lack awareness of community empowerment activities; secondly, people are unable to balance empowerment activities with their daily work. On the other hand, some people who have been mobilized in these empowerment activities acknowledge that they have gained a lot of knowledge after participating in them. Therefore, the willingness to participate is not in vain in order to improve their standard of living both now and in the future.